Enhanced biodegradation of crude oil by constructed bacterial consortium comprising salt-tolerant petroleum degraders and biosurfactant producers. (October 2020) - Chen, Weiwei; Kong, Yachao; Li, Junde; Sun, Yanyu; Min, Jun; Hu, Xiaoke
Abstract: Bioremediation is an attractive strategy of utilizing bacteria to remove crude oil contaminants. In this study, two salt-tolerant crude oil-degrading and biosurfactant-producing bacteria, Dietzia sp. CN-3 and Acinetobacter sp. HC8–3S, were functionally combined to construct a bacterial consortium. The consortium achieved 95.8% degradation efficiency of crude oil in 10 days and various n -alkanes, cycloalkanes, branched alkanes and aromatic hydrocarbons were all depleted more effectively than single strains. Functional optimization of the consortium degraded crude oil efficiently in a wide range of pH (4–10) and salinity (0–120 g L −1 ). Furthermore, two alkane hydroxylase genes, alkB in CN-3 and alkM in HC8–3S, were cloned and their expression were examined by real-time quantitative polymerase chain reaction, indicating that alkB was more prominent in long-chain alkanes (C20, C24 and C26 ) utilization and alkM played crucial roles in medium- and long-chain alkanes (C14, C16, C20, C24 and C26 ) degradation. In soil microcosms artificially contaminated with crude oil and bioaugmented with the consortium, 58.3% of total petroleum hydrocarbons were depleted after 60 days and the degradation rate (485.8 mg kg −1 d −1 ) was higher than those reported in previous studies. Consequently, the consortium is a promising candidate in crude oil bioremediation. Highlights: Crude oil degraders and biosurfactant producers were mixed to construct a bacterial consortium. The consortium achieved 95.8% degradation efficiency of crude oil in 10 days. The consortium degraded crude oil efficiently in a wide range of pH (4–10) and salinity (0–120 g L −1 ). Alkane hydroxylase genes ( alkB and alkM ) were cloned and examined by RT-qPCR for mechanism study. Bioaugmentation of consortium enhanced TPH depletion in crude oil-contaminated soil microcosms.